Characterization of PD-1 and PD-L1 Expression in Papillary Renal Cell Carcinoma: Results of a Large Multicenter Study - Erlmeier, Franziska; Steffens, Sandra; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Clinical Genitourinary Cancer, 2020)
Background: Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) play a decisive role as prognostic markers in clear-cell renal cell carcinoma (RCC). To date, the role of PD-1/PD-L1 as a prognostic marker in papillary RCC (pRCC) remains scarce. Patients and Methods: Patients’ sample collection was a joint collaboration of the nationwide PANZAR consortium – a multicenter study. Medical history and tumor specimens were collected from 245 and 129 patients with pRCC types 1 and 2, respectively. Expression of PD-1 and PD-L1 was determined by immunohistochemistry in pRCC and tumor-infiltrating mononuclear cells. Results: Of 374 pRCC specimens, 204 type 1 and 97 type 2 were evaluable for PD-1 and PD-L1 expression analysis. In total, PD-1 and PD-L1 expression were found in 8 (4.9%) of 162 and 12 (7.2%) of 166 evaluable pRCC type 1 specimens. Comparably, PD-1 and PD-L1 expression were found in 2 (2.4%) of 83 and 5 (6.2%) of 81 evaluable pRCC type 2 specimens. Hardly any clinically relevant associations between PD-1 and PD-L1 positivity and clinicopathologic or clinical courses were observed, neither in pRCC type 1 nor type 2. Conclusion: The analysis of a large pRCC cohort from a multicenter consortium revealed no impact of PD-1/PD-L1 expression on prognosis in patients with pRCC with predominantly limited disease status, neither for type 1 nor type 2. However, the impact of PD-1 and PD-L1 in more advanced pRCC disease needs further elucidation. Understanding the impact of programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) expression becomes increasingly important in renal cell carcinoma (RCC) owing to increasing therapeutic implications. However, little is known in non–clear-cell RCC about the relevance of those immune checkpoint surrogates. Here, we suggest that PD-1/PD-L1 expression in papillary RCC does not have prognostic impact, neither for type 1 nor type 2. However, in advanced disease, further evaluation according to PD-1/PD-L1 is warranted.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Non-clear-cell-renal carcinoma; Papillary renal cell; PD-1; PD-L1; Renal cell carcinoma